2014
DOI: 10.3389/fpsyg.2014.01409
|View full text |Cite
|
Sign up to set email alerts
|

Influence of context-sensitive rules on the formation of orthographic representations in Spanish dyslexic children

Abstract: Spanish-speaking developmental dyslexics are mainly characterized by poor reading fluency. One reason for this lack of fluency could be a difficulty in creating and accessing lexical representations, because, as the self-teaching theory suggest, it is necessary to develop orthographic representations to use direct reading (Share, 1995). It is possible that this difficulty to acquire orthographic representations can be specifically related to words that contain context-sensitive graphemes, since it has been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…The absence of a syllable‐frequency effect on the formation of orthographic representations was unexpected and is not easy to explain, as Jiménez and Hernández () found that the presence of high‐frequency syllables facilitated word naming. The results of this study suggest that orthographic consistency is the most important factor in determining the formation of an orthographic representation, according to the evidence that transparency affects decoding skills (Seymour et al, ) and orthographic learning (Suárez‐Coalla, Avdyli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The absence of a syllable‐frequency effect on the formation of orthographic representations was unexpected and is not easy to explain, as Jiménez and Hernández () found that the presence of high‐frequency syllables facilitated word naming. The results of this study suggest that orthographic consistency is the most important factor in determining the formation of an orthographic representation, according to the evidence that transparency affects decoding skills (Seymour et al, ) and orthographic learning (Suárez‐Coalla, Avdyli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This finding is in accordance with studies in other orthographic systems (e.g. Martens & de Jong, ) and complements other recent studies of the reading of Spanish dyslexic children (Suárez‐Coalla, Avdyly et al ., ; Suárez‐Coalla, Ramos et al ., ), which showed that children with dyslexia have difficulty storing orthographic representations both when stimuli are presented in the context of a story and when they are presented in isolation, probably because children with dyslexia have difficulty learning and automating the alphabetic code (Suárez‐Coalla & Cuetos, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations